Characterization and oxidation resistance of additive manufactured and forged IN718 Ni-based superalloys. (September 2018) - Juillet, C.; Oudriss, A.; Balmain, J.; Feaugas, X.; Pedraza, F.
Graphical abstract: The Cr2 O3 oxide scales grown after 48 h of exposure to air at 800 °C depend on the manufacturing process of IN-718 Ni-based superalloy: (a) forged and small grained; (b) forged and large grained and (c) additive manufactured. Highlights: Forged and additive manufactured IN-718 underwent similar oxidation kinetics for 48 h at 600 and 700 °C in air and in Ar. At 800 °C, the additive manufactured oxidized faster than the forged IN-718 but the kinetics became quite steady after 10 h. Inward growth prevailed in the additive manufactured IN-718 while the forged IN-718 grew oxide protrusions at the surface. The additive manufactured IN-718 established more compact scales than the forged one. The Cr2 O3 scale had columnar microstructure in the forged IN-718 but was equiaxed in the additive manufactured. Abstract: The effect of the manufacturing process (additive manufacturing and forging) of IN-718 Ni-based superalloys was studied isothermally at 600, 700 and 800 °C for 48 h in Ar and in air. The microstructure of the Cr2 O3 scale depended on the manufacturing process. Oxygen was soaked in the bulk of the additive manufactured IN-718 and outward cation diffusion was blocked. Diffusion of oxygen occurred through the grain boundaries of the forged material but cation outward diffusion was not arrested. The oxide scales grown in the forged IN-718 appeared less compact than those grown on the additive manufactured as shown by hydrogen charging experiments.